Hybrid optical measurement system for evaluation of precision two-dimensional planar stages. (15th May 2022) - Kim, Jong-Ahn; Lee, Jae Yong; Kang, Chu-Shik; Woo, Jae Heun
Highlights: Hybrid optical measurement system was developed for evaluation of 2D planar stages. Hybrid sensor module can be operated as a profile interferometer or an angle sensor by switching data-processing mode. Multiple performance indices of 2D planar stage can be evaluated without reconfiguration of the setup. Straightness and angular motion errors were measured with expanded uncertainty ( k = 2) of 40 nm and 0.14″, respectively. The proposed system would be applied to on-machine calibration effectively. Abstract: This paper presents an optical measurement system, which is mainly composed of two hybrid sensor modules (HSMs), for evaluation of precision two-dimensional (2D) planar stages. The HSM is designed to integrate two different types of sensors within a single sensor module, so that it can be operated as a profile interferometer or an angle sensor by simply switching the data-processing mode. This enables us to implement efficient on-site evaluation of straightness errors of moving mirrors of a two-axis laser interferometer, and multi-axis parasitic motion errors of a 2D planar stage without reconfiguration of the evaluation setup. To estimate the performance of a prototype measurement system, an exemplary 2D stage was experimentally evaluated, and the straightness and angular motion errors were measured with expanded uncertainty ( k = 2) of 40 nm and 0.14″, respectively. Reliability of the measurement system was also verified by comparison with reference instruments.